Fragmentation: loss of global coherence or breakdown of modularity in functional brain architecture? - van den Berg, Daan; Gong, Pulin; Breakspear, Michael; van Leeuwen, Cees (Frontiers in Systems Neuroscience, 2012)
Psychiatric illnesses characterised by disorganized cognition, such as schizophrenia, have been described in terms of fragmentation and hence understood as reduction in functional brain connectivity, particularly in prefrontal and parietal areas. However, as graph-theory shows, relatively small numbers of nonlocal connections are sufficient to ensure global coherence in the modular small world network structure of the brain. We reconsider fragmentation in this perspective. Computational studies have shown that for a given level of connectivity in a model of coupled nonlinear oscillators, modular small-world networks evolve from an initially random organization. Here we demonstrate that with decreasing connectivity, the probability of evolving into a modular small-world network breaks down at a critical point, which scales to the percolation function of random networks with a universal exponent of α=1.17. Thus, according to the model, local modularity systematically breaks down before there is loss of global coherence in network connectivity. We therefore propose that fragmentation may involve, at least in its initial stages, the inability of a dynamically evolving network to sustain a modular small-world structure. The result is in a shift in the balance in schizophrenia from local to global functional connectivity.